2020
DOI: 10.3389/fonc.2020.00054
|View full text |Cite|
|
Sign up to set email alerts
|

The Emerging Role of the c-MET-HGF Axis in Non-small Cell Lung Cancer Tumor Immunology and Immunotherapy

Abstract: Study of the c-Met-HGF axis in non-small cell lung cancer (NSCLC) has focused on the roles of c-MET signaling in neoplastic epithelial cells and the secretion of its ligand hepatocyte growth factor (HGF) by tumor stromal cells. However, there is increasing evidence that some leukocyte subsets also express c-MET raising the possibility of an immunomodulatory role for this axis. Consequently, the role of the c-MET-HGF axis in immunoncology is an active area of ongoing research. This review summarizes current kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 74 publications
0
14
0
1
Order By: Relevance
“…Also, it is established that HGF induces macrophage transition to the M2 phenotype, which is pro-generative. However, several studies have suggested that HGF could also have a pro-immune role [36,37] and further research is needed to better understand the exact role of HGF in anti-tumour immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is established that HGF induces macrophage transition to the M2 phenotype, which is pro-generative. However, several studies have suggested that HGF could also have a pro-immune role [36,37] and further research is needed to better understand the exact role of HGF in anti-tumour immune response.…”
Section: Discussionmentioning
confidence: 99%
“…MET amplification has been reported as a rare, potentially actionable, primary oncogenic driver in a subset of patients with NSCLC, with frequency depending on the definition used. 1 This is separate from its role as an acquired resistance pathway to tyrosine kinase inhibitors (TKIs) in NSCLC 2,3 or as a concurrent alteration within patients with MET exon 14 with NSCLC. 4,5 In patients with MET exon 14-altered NSCLC, reported objective responses to MET inhibition do not seem to be influenced by the absence, presence, or levels of concurrent MET amplification.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the nCounter technique can accurately analyze mRNA from formalin-fixed, paraffin-embedded (FFPE) tissue, with results similar to fresh frozen tissue [ 18 , 19 ]. MET receptor tyrosine kinase alterations have previously been shown to correlate with expression of immunoregulatory molecules, including PD-L1, and may play a role in immune evasion [ 20 , 21 ]. Therefore, this study was conducted to investigate the expression of immune markers in solid tumors with MET alterations to identify markers that may be associated with tumorigenesis.…”
mentioning
confidence: 99%